Use of Mirror Therapy for Phantom Limb sensation: A case study from Nepal (Journal of Psychiatrists' Association of Nepal, 2026)
Introduction: Phantom Limb Sensation (PLS) and Phantom Limb Pain (PLP) are frequently reported after amputation, with prevalence as high as 76–87%¹. Mirror therapy (MT) is an affordable intervention used globally to reduce PLP and PLS², but published evidence from Nepal is limited.Case Description: A 17-year-old female underwent below-elbow amputation following a road traffic accident and subsequently developed PLP with a clenching–type phantom hand posture. A two mirror setup placed at a right angle was used to create a clear visual illusion of the missing limb. Mirror therapy was conducted for 15 minutes, three times daily.Discussion: The patient showed rapid improvement in her symptoms in eight days. There was partial relief by Day 6 and complete resolution of pain by Day 8. Lack of long-term follow-up is a limitation.Conclusion: Our case highlights that mirror therapy is a simple, cost-effective technique with meaningful benefit for PLP for short-term, especially in young patients with early initiation of therapy. This case supports its feasibility and encourages its use in resource-limited Nepalese clinical settings.